Relationship Between Academic Burnout and Academic Resilience Manifest in Prospective Counselors During the New Normal Era - Rachmawati, Indriyana; Farozin, Moh; Basuki, Agus (Jurnal Kajian Bimbingan dan Konseling, 2024)
Academic resilience has become an interesting topic of discussion as a result of the increase in academic burnout experienced by prospective counselors recently as a result of increasing academic assignments. Prospective counselors who experience academic burnout generally have poor academic resilience because they feel tired or bored with academic tasks while still studying, and this has an impact on the resulting performance. This research aims to determine the relationship between academic burnout and the academic resilience of prospective counselors. We used a quantitative research method, employing a correlation research design, to reveal the relationship between the two. The research sample involved 105 prospective counselor students in Indonesia taken using convenience sampling techniques. The research sample's data collection method employed a scale measuring academic burnout and academic resilience. The data was analyzed using the Pearson Product Moment method. The research results show that academic resilience has a negative relationship with academic burnout. This means that the higher the academic resilience that a prospective counselor has, the lower the academic burnout they experience, and conversely, the lower the academic resilience of a prospective counselor, the lower the academic burnout.